Innovating organ delivery to improve access to care: surgeon perspectives on the current system and future use of unmanned aircrafts. Issue 1 (23rd November 2020) - Talaie, Tara; Niederhaus, Silke; Villalongas, Ester; Scalea, Joseph
Abstract : Objective: Organ transportation requires innovation. We recently showed that unmanned aircraft systems (UAS) could transport human organs. There are no data addressing UAS acceptance among healthcare providers. Conceptually, UAS implementation may improve delivery of care through improved efficiency. We sought to learn surgical perspectives on current and innovated organ transport systems. Methods: An Institutional Review Board exempt, pretested, 5-point Likert scale web-based survey was undertaken. Transplant surgeons taking kidney transplant offers in the USA (n=174) were sampled. Results: Of 174 surveys, 122 were delivered successfully, and 55 responses collected. Mean age was 48.1 (range 34–64), and 80% were male. Forty-two (76.4%) surgeons felt cold ischaemia time reduction to 8 hours would increase organ acceptance rates. More than 23% of respondents were fearful and 34.5% nervous regarding drones. Nearly all (92.7%) respondents believed drones could help people; 90.9% felt the mode of transportation was irrelevant to their decision to accept an organ but that speed and quality were most important. Only 16.4% of surgeons believed the current system is adequate for our transportation needs. Conclusions: Surgeons feel the present system of organ transportation needs reform, and an innovated system using UAS might improve care. An innovated organ transportation system involving UAS may lead to fear and anxiety among transplant surgeons, suggesting that research and education are required ahead of adoption.